A review of cases received by the Nepal Ambulance Service over one year. (2nd June 2021) - Peskett, Anna Rebekah; Williams, Jonathan; Thapa, Kulesh
Abstract : Nepal Ambulance Service (NAS) callout data was examined to aid future research into Nepali prehospital care, and identify trends and areas within NAS that may benefit from further training. A retrospective search was carried out of the NAS covering of the calls received and attended by NAS covering a period of 12 months. A total of 5486 cases from the NAS database were included. The data showed there had been a rise in NAS cases over the 12-month period, with 152 more cases being logged in July 2019 than in August 2018, an overall increase of 38.48%. The rise is fairly uniform and consistent month-on-month, except for February 2019, when there was an unexplained reduction. This rise is fairly uniform and consistent, except for February 2019, when there was an unexplained reduction. Respiratory and trauma were the most numerous types of case. The increase in cases is most likely because NAS is growing in popularity. Based on the findings of this paper, it would seem that NAS is set to continue its upward trajectory of callouts. Further research on this service is warranted.